English Teachers' Perception toward the Use of Google Classroom at Junior High School 2 Samarinda - Effendi Limbong; Rahman; Asih (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2024)
Google Classroom is a digital platform developed by Google to replicate the traditional classroom experience in an online environment. This study aimed to explore the perspectives of English educators at Junior High School 2 Samarinda on their use of this platform as an alternative to conventional classroom teaching. A qualitative case study design was employed for this research. The participants included two English teachers from Junior High School 2 Samarinda, selected based on specific criteria. In-depth interviews were utilized as the data collection instrument for this study. The findings revealed that both English teachers held a positive view of the platform as a substitute for traditional classrooms. This favorable perception was attributed to several factors, including the platform's user-friendliness, its capacity to enhance English teachers' workflow, the presence of a private comment section, and the ability to monitor students' assignments effectively.